The Phenomenon of Thunder in the Qur'an: A Semiotic Analysis of Roland Barthes - Fikri Ys, Irsyad Al; Taufiq, Wildan (UIN Sunan Gunung Djati Bandung, 2023)
This article aims to reveal the meaning of symbolism about the phenomenon of thunder and to uncover the symbolic meaning behind the verses that mean thunder in the Alquran. The background of the writing of this article originated from phenomenon thunder that occurs naturally and is mentioned in the Qur'an as well as being one of the names of the special surahs with the word Ar-Ra'd and its equivalent, from these findings, the writing of this article will reveal the symbolic meaning behind it. thunder phenomenon mentioned in the Koran. The semiotic theory used is the semiological theory initiated by Roland Barthes. This research methodology uses a literature study. The semiotic research results on the verses that mean thunder in the Alquran do not only have symbols as threats and punishment but also as a symbol of warning that Allah has given to mankind to be used as lessons. As well as a symbol of dhikr, so that people will always remember Allah SWT from the phenomenon of thunder.